2011
DOI: 10.1097/iae.0b013e3182083beb
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Evaluation Using Enhanced Depth Imaging Spectral-Domain Optical Coherence Tomography in Vogt–koyanagi–harada Disease

Abstract: Enhanced depth imaging spectral-domain OCT highlights a loss of focal hyperreflectivity in the inner choroid of eyes with VKH, a feature that is consistently observed by independent masked observers. The presence of this feature in both acute and convalescent phases could represent permanent structural change to small choroidal vessels caused by VKH uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(147 citation statements)
references
References 15 publications
4
132
0
11
Order By: Relevance
“…There was a statistically significant increase in choroidal thickness in the acute phase compared with that in the convalescent phase by 151 lm and compared with normal by 137 lm. The thickening returned to normal in the convalescent phase [109].…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 89%
See 3 more Smart Citations
“…There was a statistically significant increase in choroidal thickness in the acute phase compared with that in the convalescent phase by 151 lm and compared with normal by 137 lm. The thickening returned to normal in the convalescent phase [109].…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 89%
“…It is known that the retinal findings observed in VKH disease are secondary to choroidal inflammation [107,108]. Fong et al [109] used EDI SD OCT to examine the choroid of VKH patients in the acute and convalescent stages and to compare the findings with control subjects. The authors observed multiple hyperreflective dots in the inner choroid that increased in number towards the Bruch membrane in normal control eyes and speculated that these hyperreflective dots represent cross-sectional views of parallel-lying pericapillary arterioles and venules.…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The choroid appears to be primarily affected in VKH disease initially; therefore, rebound choroidal thickening seen on EDI-OCT images could be regarded as recurrent VKH disease, as in the current case, despite no clinical evidence of recurrent ocular inflammation. Furthermore, Fong et al [9] reported that EDI-OCT highlighted a loss of focal hyperreflectivity in the inner choroid of…”
Section: Discussionmentioning
confidence: 99%